Hypoxic Hypoxia and Brain Function in Military Aviation: Basic Physiology and Applied Perspectives - Shaw, David M.; Cabre, Gus; Gant, Nicholas (Frontiers in Physiology, 2021)
Acute hypobaric hypoxia (HH) is a major physiological threat during high-altitude flight and operations. In military aviation, although hypoxia-related fatalities are rare, incidences are common and are likely underreported. Hypoxia is a reduction in oxygen availability, which can impair brain function and performance of operational and safety-critical tasks. HH occurs at high altitude, due to the reduction in atmospheric oxygen pressure. This physiological state is also partially simulated in normobaric environments for training and research, by reducing the fraction of inspired to achieve comparable tissue oxygen saturation (normobaric hypoxia). Hypoxia can occur in susceptible individuals below 10,000 ft (3,048 m) in unpressurised aircrafts and at higher altitudes in pressurised environments when life support systems malfunction or due to improper equipment use. Between 10,000 ft and 15,000 ft (4,572 m), brain function is mildly impaired and hypoxic symptoms are common, although both are often difficult to accurately quantify, which may partly be due to the effects of hypocapnia. Above 15,000 ft, brain function exponentially deteriorates with increasing altitude until loss of consciousness. The period of effective and safe performance of operational tasks following exposure to hypoxia is termed the time-of-useful-consciousness. Recovery of brain function following hypoxia may also lag beyond arterial reoxygenation and could be exacerbated by repeated hypoxic exposures or hyperoxic recovery. This review provides an overview of the basic physiology and implications of hypoxia for military aviation and discusses the utility of hypoxia recognition training.